2017
DOI: 10.1111/bjep.12180
|View full text |Cite
|
Sign up to set email alerts
|

Sleep difficulties and academic performance in Norwegian higher education students

Abstract: Self-reported sleep difficulties are associated with poorer objective markers of academic outcomes as well as poorer self-rated academic proficiency among higher education students. Amelioration of sleep difficulties may improve overall academic performance and health outcomes in affected students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…The finding that insomnia was associated with failed study examinations are in line with those of the previous SHoT survey from 2014, where a single item measuring DIMS was associated with failing several examinations [16]. The present study support and further expand on these findings, and provides additional specificity with regards to an approximation of the DSM-5 insomnia disorder.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that insomnia was associated with failed study examinations are in line with those of the previous SHoT survey from 2014, where a single item measuring DIMS was associated with failing several examinations [16]. The present study support and further expand on these findings, and provides additional specificity with regards to an approximation of the DSM-5 insomnia disorder.…”
Section: Discussionsupporting
confidence: 91%
“…One item on DIMS was omitted from the composite score and replaced with the mean of the remaining items, thereby preserving the recommended total score to enable comparison with other studies. Reliability analyses of HSCL-25 (without the sleep item) yielded a Cronbach's alpha of 0.93, which is comparable to previous psychometric assessments of this modified scale [16].…”
Section: Psychological Distresssupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, some key findings from the SHoT2014 have been published in peer-reviewed international journals: Examining the psychometric properties of the included measure of mental health problems, the Hopkins Symptoms Check List (HSCL-25),14 Skogen et al concluded that a unidimensional model was most appropriate for HSCL-25 in student populations 15. Investigating sleep problems in college students, Hayley et al found that difficulties initiating or maintaining sleep was linked to increased risk of both social and emotional loneliness,16 as well as poorer academic outcomes and poorer self-rated academic proficiency 17. And focusing on the introductory week offered by most Norwegian higher education institutions, Myrtveit et al found that 7 of 10 students were satisfied with the introductory week, and that participation in the event was associated with better social integration, although some felt excluded due to the amount of alcohol involved 18 19…”
Section: Findings To Datementioning
confidence: 99%
“…epidemiology, sleep disturbance, student, trend 1 | INTRODUCTION Short sleep duration and insomnia have both been highlighted as major public health problems (Barnes & Drake, 2015). The high rate of sleep problems (Gress-Smith, Roubinov, Andreotti, Compas, & Luecken, 2015;Hayley, Skogen, Overland et al, 2015), and the wide range of well-demonstrated consequences for both mental (Glozier et al, 2010;Stefan, Juranko, Prosoli, Baric, & Sporis, 2017) and physical health (Hasler et al, 2004;Kecklund & Axelsson, 2016), as well as impaired function (Hayley, Sivertsen, Hysing, Vedaa, & Overland, 2017), have led to increased awareness of the importance of getting sufficient goodquality sleep.…”
Section: Introductionmentioning
confidence: 99%